THE USE OF SEMANTIC WORD MAPPING IN VOCABULARY TEACHING - Coto, Rian Yusniarsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The research investigated the use of semantic word mapping technique in vocabulary teaching. The research investigated the evidence that this technique was useful to use in vocabulary teaching. The researcher formulated two hypotheses, namely null hypothesis and alternative hypothesis. The research method was a pre experimental research with one group pre-test and post-test design. The sample of the research was 32 out of 40 students of class VIII E. The data were collected by objective tests and analyzed by paired t-test and effect size formula using Cohen?s index. After analyzing the research data, the null hypothesis (H0) was rejected, while alternative hypothesis (Ha) was accepted. The t absolute (4.16) was bigger than t critical (1.697) by degree of freedom 31. The effect size is categorized as large effect since the r value was 0.95 that was bigger than 0.80. The conclusion was the use of semantic word mapping in vocabulary teaching, a pre-experimental study on the eighth grade students of SMP Negeri 5 Pontianak in Academic Year 2015/2016 was significant and has large effect.Key words: Semantic Word Mapping, Vocabulary Teaching, Vocabulary Meaning Abstrak: Penelitian ini menginvestigasi kegunaan tehnik Semantic Word Mapping dalam pengajaran kosakata. Peneliti merumuskan dua hipotesis, yaitu hipotesis nol dan hipotesis alternative. Metoda penelitian yang digunakan adalah penelitian pre eksperimen dengan satu grup pre-test dan post-test. Sampel penelitian ini adalah 32 siswa dari 40 siswa kelas VIII E. Data diperoleh dengan menggunakan objektif tes dan dianalisis menggunakan uji-t berpasangan dan ukuran efek menggunakan rumus indeks Cohen. Setelah menganalisis data penelitian, hipotesis nol (H0) ditolak, sedangkan hipotesis alternatif (Ha) diterima. Nilai t hitung (4.16) lebih besar daripada t tabel (1.697) dengan derajat kebebasan 31. Ukuran efek dikategorikan sebagai efek besar karena nilai r nya adalah 0.95, lebih besar dibandingkan 0.80. Kesimpulanya adalah penggunaan tehnik Semantic Word Mapping dalam pengajaran kosakata, sebuah penelitian pre-eksperimen pada murid kelas 8 SMP Negeri 5 Pontianak pada tahun akademik 2015/2016 adalah penting dan sangat efektif.Kata Kunci: Semantic Word Mapping, Pengajaran Kosakata, Makna Kata